2021
DOI: 10.1002/jgm.3383
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation characterization and possible candidate genes in miscarriage and stillbirth by next‐generation sequencing analysis

Abstract: Background: The present study aimed to explore the etiological relationship between miscarriage and stillbirth and copy number variations (CNVs), as well as provide useful genetic guidance for high-risk pregnancy.Methods: In total, 659 fetal samples were recruited and subjected to DNA extraction and CNV sequencing (CNV-seq), relevant medical records were collected.Results: There were 322 cases (48.86%) with chromosomal abnormalities, including 230 with numerical abnormalities and 92 with structural abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
1
5
1
Order By: Relevance
“…The study detected 138 cases (34.94%) of autosomal trisomy, accounting for 52.08% of the abnormal karyotypes. Among the cases with chromosomal trisomy, chromosome 16 was found to be the most common site, the trisomy of chromosome 16 was observed in 36 cases, accounting for 19.25% (36/187) of all numerical abnormalities, this result is consistent with previous research ( 30 , 31 ). The second most common trisomy was chromosome 22, which was found in 22 cases, accounting for 11.76% (22/187) of all numerical abnormalities.…”
Section: Resultssupporting
confidence: 91%
“…The study detected 138 cases (34.94%) of autosomal trisomy, accounting for 52.08% of the abnormal karyotypes. Among the cases with chromosomal trisomy, chromosome 16 was found to be the most common site, the trisomy of chromosome 16 was observed in 36 cases, accounting for 19.25% (36/187) of all numerical abnormalities, this result is consistent with previous research ( 30 , 31 ). The second most common trisomy was chromosome 22, which was found in 22 cases, accounting for 11.76% (22/187) of all numerical abnormalities.…”
Section: Resultssupporting
confidence: 91%
“…In the characteristic of maternal age, we noticed that 228 cases were < 35 years old, while only 33 cases were ≥ 35 years old. Many previous studies reported that the frequency of total chromosomal abnormalities was significantly higher in the group with advanced maternal age than in the group with younger maternal age (Gu et al, 2021;Ozawa et al, 2019;Wang et al, 2017Wang et al, , 2020Zhang, Huang, et al, 2021), while no significant difference was found in our study. The nonsignificant difference might be due to the uneven distribution of maternal age.…”
Section: Discussioncontrasting
confidence: 91%
“…In this study, combined STR and CNV-seq testing detected a homozygous phenomenon in the 2p25.3q37. chromosomal testing of fetuses aborted, mostly used in the detection of chromosome number abnormalities, large fragment deletion/duplication, and copy number variation of pathogenic genomes [19] . Although chromosomal karyotyping is considered the gold standard for detecting chromosomal abnormalities, it cannot detect deletions/duplications smaller than 5-10Mb.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased SAC expression also leads to errors in sister chromatid separation during the second meiotic division (MII) of oocytes, thereby increasing the incidence of early embryonic aneuploidy(SHIMOI et al, 2019). In this study, the rate of chromosomal abnormalities in aborted tissues in the ≥ 35 age group accounted for 58.8%, and the rate of chromosomal abnormalities in the < 35 age group accounted for 48.7%, Although the difference was not statistically signi cant (P = 0.451), the abnormality rate in the ≥ 35 group was 10.1% higher than that in the < 35 group, indicating a positive correlation between the frequency of abnormal karyotypes and maternal age.Chromosomal abnormalities in fetuses aborted in the rst trimester may involve any one or multiple chromosomes, although chromosomal abnormalities in fetuses aborted in the second trimester may be trisomy 13, 18, and 21, sex chromosome aneuploidy, or CNV, which are similar to the types of chromosomal aberrations detected in live birth(ZHANG et al, 2021;LAN et al, 2021). With the development of molecular biology technology, CNV-seq technology has been gradually applied to…”
mentioning
confidence: 99%